Assembling the socio-educational spheres within contested urban environments: The Role of a Community Learning Hub in a Contested Urban Environment - Combrinck, Carin (University of Pretoria, 2021)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2020.